Expedición a Valdivia - Guerra Pedrosa, Gilberto (Rechtsgeschichte : Rg : Zeitschrift des Max-Planck-Instituts für Europäische Rechtsgeschichte, 2020)
Mark Meuwese, To the Shores of Chile: The Journal and History of the Brouwer Expedition to Valdivia in 1643 (Latin American Originals), State College: The Pennsylvania State University Press 2019, 136 p., ISBN 978-0-271-08375-9